Association Study of Apolipoprotein E Gene Polymorphism With Incidence and Delayed Resolution of Hemifacial Spasm - Zhou, Jianxin; Jiang, Li; Yuan, Sangui; Huang, Jiashang; Shi, Quanhong; Xie, Yanfeng; Deng, Bo; Zhan, Yan (Frontiers in Neurology, 2021)
Objective: This study investigates the correlation between Apolipoprotein E gene (APOE) polymorphism and incidence and delayed resolution of hemifacial spasm. Methods: The APOE genotypes of 151 hemifacial spasm patients and 73 control cases were determined by cleaved amplification polymorphism sequence-tagged sites. The distribution of three APOE alleles (ε2, ε3 and ε4) in two groups and the delayed resolution rate in 6 genotypes were calculated and statistically analyzed. Results: The proportion of patients with APOE ε3/ε4 genotype in hemifacial spasm group (25.17%) was significantly higher than that in control group (12.33%) (P=0.027). In terms of allele frequency, the proportion of APOE ε4 allele in hemifacial spasm group (15.56%) was significantly higher than that in control group (6.85%) (P=0.009). Meanwhile the proportion of APOE ε4 allele carriers in hemifacial spasm group (29.80%) was significantly higher than that in control group (13.7%) (P=0.009). Logistic regression analysis showed that the ε4 allele significantly increased the incidence of hemifacial spasm (OR 2.675, 95%CI 1.260-5.678, P=0.010). Among the 32 patients with delayed resolution, the ε3/ε3 and ε3/ε4 had the highest proportion in 6 genotypes. The delayed resolution rate of APOE ε3/ε4 (34.21%) was significantly higher than APOE ε3/ε3 (17.78%) (P<0.05). The delayed resolution rate of APOE ε4 carriers was the highest (33.33%) in the 3 allele carriers, but there was no significant difference among the 3 allele carriers (P=0.065). Conclusion: The polymorphism of APOE is relevant to the incidence rate of hemifacial spasm. APOE ε4 allele increases the incidence of hemifacial spasm. The APOE ε4 allele may promote the occurrence of delayed resolution.